Analisis dan Perancangan Sistem Mediation dengan Protokol Soap pada Web Service untuk Mengintegrasikan Antar Sistem Informasi yang Berbeda Platform - Muhamad Femy Mulya; Nofita Rismawati (ULTIMA InfoSys, 2017)
Web service is actually a collection of functions and methods contained on a server that can be called by the client remotely, then to call those methods we are free to use applications that will be created with any programming language that run on any platform. The existence of web service technology can bridge the technological differences of each source. The purpose of this system design is to build a mediation system that can integrate different information systems platforms, databases and functions, so that can communicate between systems. Software development methods used include three main parts of the method of analysis, design and literature study. Methods of analysis include the collection of data using samples, learning on existing systems, and analysis of the results of interviews aimed at the parties concerned. Design method using Unified Modeling Language (UML) approach. The result is a system-based mediation system design using the SOAP (Simple Object Access Protocol) protocol. Index Terms— Web Service, Mediation